Evaluasi Pelaksanaan Kurikulum Tingkat Satuan Pendidikan (KTSP) Sekolah Menengah Pertama (Smp-Mts) di Kota Pekalongan Tahun 2011 - Muhammad Ali Gunawan; Fajru Sidqi; M. Haryanto; Dwi Eddy Wibowo (Delta: Jurnal Ilmiah Pendidikan Matematika, 2013)
This study aims to determine and describe and evaluate: 1) Implementation of the School Based Curriculum (SBC) in Junior High School in Pekalongan from the context, input, process, and product; 2) the obstacles faced by schools in implementation of School Based Curriculum (SBC) in junior High School in Pekalongan. From 35 Junior high schools in Pekalongan, 10 (ten) schools was taken as the sample in this study using multistage sampling technique. Data analysis techniques used were descriptive statistics for the primary data (quantitative) and qualitative for secondary data. This study shows that: 1) viewed from 8 national education standards, the implementation of School Based Curriculum (SBC) in Junior High School in Pekalongan fall into the category of "good", with a mean score 1.070; 2) the impact of SBC on the Education Quality of junior high school in Pekalongan from the National Examination and Final Examination schools can not be concluded because most schools still adopt the curriculum issued by BSNP; 3) Constraints faced by schools in implementing the curriculum in junior high school in Pekalongan are: (1) the schools have not been able to perform context analysis, analysis of opportunities and challenges optimally, (2) the school autonomy is low, (3) the schools have not been able to conduct self-evaluation based on the condition of the existing schools, (4) the means and infrastructure to support the implementation of the curriculum are still inadequate, especially in private schools, (5) many teachers are still teaching in some schools so that they can not focus on school development, (6) the ability of teachers in preparing and developing assessment instruments are low.